Effect of Age on Nitric Oxide Level in Murrah Buffalo (Bubalus bubalis) Neonates - SINGH, ANIL KUMAR; PANDITA, SUJATA; CHANDRA, GULAB; MAURYA, PANKAJ KUMAR; CHAUDHARI, BIJAY KUMAR (Indian Journal of Dairy Science, 2014)
Immune system of calf is more susceptible to oxidative stress during neonatal period due to immature defense system against superoxide radicals. Nitric oxide (NO), a component of bactericidal mechanisms of phagocytic leukocytes, plays a pivotal role in cell-mediated immunity. Present research has addressed many NO-related aspects of neonatal adaptation in the postpartum period. The experiment was conducted on twenty Murrah buffaloes selected from NDRI herd. Approximately 15 ml blood was drawn in sterile heparinised vacutainer tubes from each calf born from these buffaloes, by jugular veni-puncture on day 0 (Before colostrum feeding), followed by day 1, 3, 7, 14, 21, 28, 42, 56, 70, 84, 98, 112 and 126 post birth at 6.00 AM in the morning. Plasma was aliquoted and analysed for total NO by modified Griess Reaction as described by Shoker and coworker. Plasma nitrate and nitrite levels were significantly elevated (P